أثر الثقافة التنظيمية في تعزيز عمليات إدارة المعرقة - قحف عقيلة; جديدي مريم; وفاء شعوبي (university of eloued جامعة الوادي, 2025)
"الملخـــــــــص تهدف الدراسة إلى التعرف على مدى تأثير الثقافة التنظيمية في تعزيز عمليات إدارة المعرفة،وذلك بالاعتماد على نموذج يقيس أثر الثقافة التنظيمية بأبعادها (إدراك المعرفة، البيئة التعاونية، الرؤية المشتركة، ممارسات الإدارة العليا) في تعزيز عمليات إدارة المعرفة من عملياتها الاستكشاف المعرفي ببعديه خلق المعرفة والتشارك المعرفي وعملية الاستغلال المعرفي. حيث أجريت الدراسة الميدانية في مؤسسة سونلغاز بالوادي، وقد تم استخدام الاستبيان كأداة لجمع البيانات، حيث تم توزيع 70 استبانة على عينة عشوائية من مختلف المستويات الادارية، منها 58 استبانة صالحة للدراسة، استخدمت الدراسة المنهج الاستكشافي الاختباري، وتم تقدير النموذج باستخدام البرنامج الإحصائي V 20 SPSS، وبعد تقدير النموذج توصلت الدراسة إلى أن هناك أثر للثقافة التنظيمية في تعزيز عمليات إدارة المعرفة بالمؤسسة محل الدراسة من خلال بعد البيئة التعاونية فقط. "Summary: The study aims to highlight the impact of organizational culture on enhancing knowledge management processes, relying on a model that reflects the impact of organizational culture in its dimensions (knowledge perception, collaborative environment, shared vision, and senior management practices) on enhancing knowledge management processes represented by the knowledge exploration process with its two dimensions: knowledge creation and knowledge sharing, and knowledge exploitation. The field study was conducted at the Sonelgaz institution in El Oued. The questionnaire was used as a data collection tool, with 70 questionnaires distributed to a random sample from various administrative levels, of which 58 were valid for the study. The study used the exploratory experimental approach, and the model was estimated using the statistical program SPSS V25, After estimating the model, the study concluded that there is an impact of organizational culture in enhancing knowledge management processes in the institution under study through the dimension of the collaborative environment only."
ماستر
Keywords: ثقافة تنظيمية،; إدراك إدارة المعرفة،; بيئة تعاونية; رؤية مشتركة; ممارسات إدارة عليا،; استكشاف معرفـي; Organizational culture; Knowledge management perception; Collaborative Environment; Shared vision; Senior management practices; Knowledge exploration; Knowledge exploitation; Sonelgaz.